Male histone deacetylase 6 (HDAC6) knockout mice have enhanced ventilatory responses to hypoxic challenge - Getsy, Paulina M.; Coffee, Gregory A.; Kelley, Thomas J.; Lewis, Stephen J. (Frontiers in Physiology, 2024)
Histone deacetylase 6 (HDAC6) is a class II histone deacetylase that is predominantly localized in the cytoplasm of cells. HDAC6 associates with microtubules, regulating acetylation of tubulin and other proteins. The possibility that HDAC6 participates in hypoxic signaling is supported by evidence that (1) hypoxic gas challenges cause microtubule depolymerization, (2) expression of hypoxia inducible factor alpha (HIF)-1 alpha is regulated by microtubule alterations in response to hypoxia, and (3) inhibition of HDAC6 prevents HIF-1 alpha expression and protects tissue from hypoxic/ischemic insults. The aim of this study was to address whether the absence of HDAC6 alters ventilatory responses during and/or after hypoxic gas challenges (10% O2, 90% N2 for 15 min) in adult male wildtype (WT) C57BL/6 mice and HDAC6 knock-out (KO) mice. Key findings were that (1) baseline values for frequency of breathing, tidal volume, inspiratory and expiratory times and end expiratory pause were different between KO mice and WT mice, (2) ventilatory responses during hypoxic challenge were more robust in KO mice than WT mice for recorded parameters including, frequency of breathing, minute ventilation, inspiratory and expiratory durations, peak inspiratory and expiratory flows, and inspiratory and expiratory drives, and (3) responses upon return to room-air were markedly different in KO compared to WT mice for frequency of breathing, minute ventilation, inspiratory and expiratory durations, end expiratory pause (but not end inspiratory pause), peak inspiratory and expiratory flows, and inspiratory and expiratory drives. These data suggest that HDAC6 may have a fundamentally important role in regulating the hypoxic ventilatory response.